PENGGUNAAN PENDEKATAN DISCOVERY UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI GERAK BENDA BERDASARKAN PENGGUNAANNYA - Malinda, Dini; Panjaitan, Regina Lichteria; Sujana, Atep (Jurnal Pena Ilmiah, 2017)
Student learning outcomes are the most important thing in learning activities. The success of students in learning is influenced by the ferformance of good teachers and the activity of student in classroom, especially in science lessons that emphasizes students to play an active role during learning activitis. One the learning approaches that can be used to improve student activity in classroom is Discovery approach. This research was conducted using PTK, and model used is spiral Kemmis and Mc. Taggart. Discovery approach. Subject research are student SDN Sukasirna II subdistrict Sumedang Selatan residential Sumedang. Instrument in this study are observation guidelines ferformance teacher, activities student, test results, interview teacher, interview student, field notes, and dokumentation. Based on the results of research using Discovery approach can improve student learning outcomes. This can be see in the creasestudent learning outcomes.